Research Status of Caenorhabditis elegans Model in Toxicology and Its Applications in Forensic Science - LI Zhuo; ZENG Yi-ru; SHU Zhi-long; SUN Xue-hong; ZHANG Kui (Fayixue Zazhi)
Caenorhabditis elegans, as an emerging model organism, has been widely used in multiple disciplines such as medicine, life science, and environmental science in recent years, due to its characteristics of short life cycle, clear genetic background, highly conserved evolution, complete genome analysis and excellent fitting between experimental data and human results. It also shows unique advantages in the field of toxicology. This paper summarizes its advantages in toxicological research starting from the biological characteristics of C. elegans, introduces the toxicological research methods and progress based on the C. elegans model, focuses on demonstrating its applications in environmental forensic medicine and forensic toxicology, and looks forward to the application of the relevant results in the field of forensic science.